Well, the only way I figured to use was using the method for 'similar triangles'
So, what I did was, since the whole of AB is similar to AD, and the whole of AC is similar to AE...
AB/AD =AC/AE
Then, since We already know AB and AC, i'll choose one as the 'unknown' to check my answer, so I chose AC i this case which has a value of 6...(You'll know what i mean in a bit) and keep substituting the values of AD and AE to check if my 'unknown' is indeed 6//
So for the first statement:
8/3 = AC/4
( solve for AC ) == 8 x 4 / 3
AC =10.6...which we know is not the value of AC, as it is 6
Second statement
8/3 =AC /6
AC =16 xxx (wrong)
Third statement
8/4 = AC/6
AC = 12 xxx
Fourth Statement
8/4 =AC/3
AC = 6, which is what we have!
So I THINK the last statement is right
P.s## I'm still a little skeptical about my method, but nonetheless hope this helps